Graphene-Based Films as Effective Mosquito Repellent for Human Skin Protection: A Brief Review - Prajapati, Anuradha Parixit; Gandhi, Shivani; Singh, Garima; Narkhede, Sachin; Luhar, Shailesh (Indian Journal of Pharmaceutical Education and Research, 2024)
Mosquito-borne diseases pose significant public health threats worldwide, necessitating effective prevention strategies. Traditional chemical agents used for mosquito bite prevention often carry environmental and health risks. In this review, we explore the potential of graphene-based films as a non-chemical approach for protecting against mosquito bites. The aim of this review is to assess the effectiveness of multilayer graphene films in preventing mosquito bites and to explore their practical implications for public health. Through experimental investigations, researchers found that dry multilayer graphene films effectively block mosquitoes’ ability to detect skin or sweat chemicals, thereby preventing mosquito bites. Additionally, these films can serve as physical barriers to the mosquito’s feeding mechanism. The findings suggest promising applications of graphene films in protective technologies for human skin and smart fabrics. Graphene’s non-toxic nature and ease of application make it an attractive alternative to chemical repellents. Implementing graphene-based films for mosquito bite prevention could potentially reduce the transmission of mosquito-borne diseases, addressing critical public health concerns. In conclusion, this review highlights the potential of graphene films as a non-chemical method for mosquito bite prevention. Future research should focus on evaluating the long-term effectiveness and safety of graphene films, paving the way for the development of innovative technologies that utilize graphene to safeguard against mosquito bites and mitigate the spread of infectious diseases.
Keywords: Graphene; Mosquito repellent; Chemo-sensing; Molecular barrier; Puncture; resistant’ s